2022
DOI: 10.3389/fonc.2022.930647
|View full text |Cite
|
Sign up to set email alerts
|

Extra Spindle Pole Bodies-Like 1 Serves as a Prognostic Biomarker and Promotes Lung Adenocarcinoma Metastasis

Abstract: Extra spindle pole bodies-like 1 (ESPL1), a cysteine endopeptidase, plays a vital role in chromosome inheritance. However, the association of ESPL1 with prognosis and immune infiltration in lung adenocarcinoma (LUAD) has not yet been explored. Here, we analyzed the expression level, prognostic values, diagnostic value, and immune infiltration level in LUAD using various databases. Immunohistochemistry (IHC) and quantitative real-time PCR (qRT-PCR) assays were used to detect the expression of ESPL1 in LUAD tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The TME composed of immune and nonimmune cells (e.g., endothelial cells), with the former accounting for the vast majority of the TME cell population [ 36 ]. The literature suggests that the composition of the TME was closely associated with tumour progression, immune evasion and the success of immunotherapy [ 13 ]. The present found that the TME composition was significantly different between the high- and low-ESPL1-expression groups and that ESPL1 expression correlated with the levels of various immune cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TME composed of immune and nonimmune cells (e.g., endothelial cells), with the former accounting for the vast majority of the TME cell population [ 36 ]. The literature suggests that the composition of the TME was closely associated with tumour progression, immune evasion and the success of immunotherapy [ 13 ]. The present found that the TME composition was significantly different between the high- and low-ESPL1-expression groups and that ESPL1 expression correlated with the levels of various immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the overexpression of ESPL1 was significantly associated with higher tumour purity and lower immune cell levels in TME. In previous studies, ESPL1 expression in LUAD was positively correlated with the level of infiltration of Th2 cells and negatively correlated with the level of infiltration of mast cells, iDCs, DCs and CD8T cells and might be involved in immune evasion and tumour migration [ 13 ]. However, there is still a gap in the mining of ESPL1 in the field of immunity, especially in BC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies, in addition to NCAPD2, 18 hub genes have also been reported to be overexpressed in lung cancer and contribute to a poor prognosis. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Subsequently, we constructed a prognostic model, which exerted a good predictive effect. The above studies further demonstrated that hub genes, including NCAPD2, jointly promote the occurrence and progression of LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were incubated with secondary antibody (MaxVision TM HRP-Polymer anti-Mouse/Rabbit IHC Kit, KIT-5030, Fuzhou, China) for 25 minutes at room temperature, finally, stained with diaminobenzidine (MaxVision, DAB-1031, Fuzhou, China). 11 IHC outcomes were assessed through two pathologists who were blinded to group allocation, and all differences were resolved through discussion.…”
Section: Immunohistochemistry Analysismentioning
confidence: 99%